The Impact of Applying Two Active Learning Strategies on Fifth Grade Students’ Achievement In History - Al-katatneh, Thekarayat Mohmmad (Journal of Educational and Psychological Sciences, 2020)
This study aimed at investigating the impact of applying two active learning strategies on the achievement of the Fifth grade students in the history course in Jordan. The researcher experimental method the sample of study consisted of (109)the fifth grade students developed an achievement test and applying them on a pilot sample and calculating their reliability using Their reliability values were (0.85).Using ANCOVA revealed a better achievement and level of Fifth grade male students who were taught history by using active discussion than who were taught the same subject using either modified lecture or traditional method. The results also showed a better achievement of Fifth grade male students who were taught history by using modified lecture than who were taught the same subject by using the traditional method. The study presented many recommendations among them: Conducting training courses for history teachers to use active learning strategies in their lesson plans.
Keywords: Active learning; Active discussion; Modified lecture; Education achievement